2023
DOI: 10.4314/jasem.v27i1.26
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Concentration of Thorn Apple (Datura stramonium) Extract on Growth, Histopathology and Blood Profiles Response to Sub- Lethal Exposure of Nile Tilapia (Oreochromis niloticus) Juveniles

Abstract: This study investigated the toxic effects of Datura stramonium leaves extract on growth, histopathology and blood profiles of Oreochromis niloticus juveniles. Datura stramonium leaves extract of various concentrations were prepared at 0.00 (control), 0.002, 0.02 and 0.2 ml/L for 28 days and 10 days withdrawal in triplicate. Twenty (20) Oreochromis niloticus fingerlings (6.05±0.01g) were randomly distributed into each experimental bowl containing 45 L of treatment concentrations. Biological evaluation, blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Similar findings to our study were reported in O. mykiss (Imani et al, 2015), and Cyprinus carpio (Lee et al, 2014). According to Olusola et al (2023) investigated the effects of thorn apple ( Datura stramonium ) extract on growth, histopathology, and blood profiles in Nile tilapia and reported that the experimental groups showed an increase in TPR and ALB values, and a decrease was observed in ALT and AST values when compared to the control group. An increase in the amount of GLU (blood glucose) in fish indicates stress (Pacheco & Santos, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings to our study were reported in O. mykiss (Imani et al, 2015), and Cyprinus carpio (Lee et al, 2014). According to Olusola et al (2023) investigated the effects of thorn apple ( Datura stramonium ) extract on growth, histopathology, and blood profiles in Nile tilapia and reported that the experimental groups showed an increase in TPR and ALB values, and a decrease was observed in ALT and AST values when compared to the control group. An increase in the amount of GLU (blood glucose) in fish indicates stress (Pacheco & Santos, 2001).…”
Section: Discussionmentioning
confidence: 99%